The Role of Islamic Spiritual Activities on Students' Spiritual Intelligence - Apriani Dolla; Ruwiah A. Buhungo; Muhammad Nur Iman; Dedi Gunawan Saputra (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine the role of Islamic Spiritual Activities (Rohis) in enhancing students' spiritual intelligence at MAN 1, Gorontalo Regency. Spiritual intelligence is understood as a person's ability to interpret life, internalize religious values, and apply them in daily behavior. As a religious organization within the school environment, Rohis plays a significant role in shaping religious character and developing students' spiritual aspects. This study used a qualitative approach with a descriptive approach. Data were collected through observation, interviews, and documentation. Informants included the principal, the Rohis advisor, the Rohis chairperson, and several students at MAN 1, Gorontalo Regency. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. To ensure data validity, the researcher used source and technique triangulation. The results indicate that Rohis activities positively contribute to enhancing students' spiritual intelligence. This is evident through various programs implemented, such as Islamic studies, Quran recitation, commemoration of Islamic holidays, religious mentoring, and social activities. These programs help students increase their awareness of worship, strengthen their relationship with God, and foster discipline, responsibility, social awareness, and good morals in their daily lives. Supporting factors for the Rohis program include support from the school, instructors, and student enthusiasm. Meanwhile, inhibiting factors include limited time and uneven student participation.